Plan Especial de Salvaguardia (PES) Como Manifestación Sociocultural e Histórica en el Camino de Las Papas, San Agustín - Huila y San Sebastián - Cauca (2023)
El Camino de las Papas, also known as Camino Nacional or El Letrero, is an ancestral route wich comunicate the distrcts of Quinchana, San Agustín - Huila and Valecia, San Sebastián – Cauca that has a high historical, cultural and environmental value that has allowed the transport and exchange of various foods, fabrics, minerals, clothing, livestock and traditions through the Macizo Colombiano since the 16th century; however, its importance at national level has gradually diminished due to the deterioration it has experienced thanks to deficient management by the State. It is for thisreason that, considering its recent declaration as Heritage and Asset of Cultural Interest of the Department of Huila, we think about the opportunity to generate a regulation or norm that allows the proper conservation of El Camino de Las Papas, its environment, historical and sociocultural memory through a PES. The project begins with the execution of an integrated approach diagnosis, where quantitative information is gathered through cartographic information tools, and qualitative Information through field work; Subsequently, the analysis of static and dynamic factors identified in the study area is developed, defining a scheme of possible interventions that allow projecting the planning and organization strategies in the rural territory to safeguard the route and the environmental, archaeological, sociocultural and historical factors that it has, framing the project in an urban-regulatory intervention on a cultural heritage.